Testing the Hypothesis of Duration Dependence in the U.S. Housing Market - Dettoni-Hidalgo, R (Elsevier Ltd, 2023)
The aim of this work is to test for duration dependence to examine rational speculative behaviour in the US housing market. Unlike other works that also test for duration dependence in stock markets, we use the Home Price Index, in a fractionally integrated model to calculate the runs of abnormal returns, and a flexible non-parametric model to estimate the hazard function of these runs. After applying the models, we conclude that the condition is not fulfilled in the US housing market. To the best of our knowledge, it is the first time that a combination of fractional integration along with a modern non-parametric duration model is applied to test for rational speculative bubbles in the US housing market. © 2023 Elsevier Inc.